Soundscape Evaluation Comparison of Outdoor Activity Space Between Gated and Open Communities - Zhu, Peisheng; Liu, Xidong; Lu, Xiaodong; Guo, Fei; Tao, Wanqi; Han, Xiaodi (Frontiers in Psychology, 2021)
In communities, outdoor activity space is utilized most often by older adults and children, and the soundscape is very important for its quality. For different community planning modes, such as gated and open communities, focus should be on different soundscape enhancement strategies for outdoor spaces. In this paper, typical samples of activity spaces in a gated community and in an open community were used. The comparison was conducted through soundscape evaluation including an analysis of the dominance of various sound sources, noise annoyance, and the perceptual dimensions of soundscape. The results showed that noise annoyance in the gated community was significantly lower than in the open community, although the noise level was of no significance between the two communities. The community planning mode moderated the relationships among the soundscape perception parameters between the gated and open communities. To reduce noise annoyance in the gated communities, each sound source should be considered; in open communities, traffic noise only should be considered. In a gated community, adding natural sounds to reduce noise annoyance may be a feasible intervention; in an open community, this is not necessary. Besides, there was no relationship between noise annoyance and Eventfulness in an open community, indicating that noise annoyance was insufficient to explain the complex sound environment of the community. China’s community planning will gradually shift from a gated community to an open community, making the soundscape of outdoor activity spaces likely to change dramatically in the future. The findings will help urban designers and managers to adopt targeted strategies to improve the soundscape and quality of life of community-dwelling older adults and children.